Recommendations for Case Learning Based of Local Wisdom Integrated with The Exo Olo Task Learning Model in Implementing The Merdeka Curriculum at Senior High School in Ambon City - Ferdinand Salomo Leuwo; Asep Asep; Dewilna Helmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning in the era of independent curriculum development is an opportunity for educators and education units to improve competence. Active and participatory learning is one of the targets in developing learning to implement the independent curriculum. Case learning is something that can be applied to realize the learning objectives of the independent curriculum. this study aims to provide recommendations for developing learning in the implementation of an independent curriculum in Ambon City Public High School. The integration of the Exo Olo Task learning model developed in local wisdom-based case learning is part of what is developed in this goal. This research was conducted in the form of descriptive qualitative research. In this case, collaboration (cooperation) with several related parties (Stake holders) to develop a local wisdom-based case learning pattern that supports the implementation of an independent curriculum in Ambon City State High School. Data obtained through observations and interviews were analyzed using qualitative research techniques using the mile and huberman method and continued with policy direction analysis through AHP method analysis. Recommendations are given with priority to 1) Increasing the use of local wisdom cases as participatory teaching materials and media, 2) Development of strategies and mastery of educators in preparing lesson plans, 3) socialization of independent curriculum-based learning programs, 4) increasing partnerships in developing learning projects and improving character through the project of strengthening the profile of Pancasila students (P5), 5) educator literacy education through reflection with outputs in the form of scientific papers with a Consistency Ratio of 0.09.